Effects of tamoxifen on the immune response phenotype in equine peripheral blood mononuclear cells - Rodríguez, Maksimiano; Quiroga, John; Cortés, Bayron; Morán, Gabriel; Henríquez, Claudio (Frontiers in Veterinary Science, 2024)
Tamoxifen (TAM) is widely utilized in the prevention and treatment of human breast cancer and has demonstrated the potential to modulate the immune response. It has been proposed as a therapeutic tool for immune-mediated diseases. TAM has been investigated as a possible treatment for asthma-like conditions in horses, revealing specific impacts on the innate immune system. While the effects of TAM on equine neutrophils are well-documented, its influence on lymphocytes and the modulation of the immune response polarization remains unclear. This in vitro study employed peripheral blood mononuclear cells (PBMC) from healthy horses, exposing them to varying concentrations of the TAM and assessing the expression of genes involved in the polarization of the immune response (TBX21, IFNG, GATA3, IL4, IL10, FOXP3, and CTLA4) in PBMC stimulated or not with PMA/ionomycin. Additionally, the effect of TAM over the proportion of regulatory T cells (Treg) was also assessed. TAM did not significantly affect the expression of these genes and Treg at low concentrations. However, at the highest concentration, there was an impact on the expression of GATA3, IL4, IL10, and CTLA4 genes. These alterations in genes associated with a Th2 and regulatory response coincided with a noteworthy increase in drug-associated cytotoxicity but only at concentrations far beyond those achieved in pharmacological therapy. These findings suggest that the effects of TAM, as described in preclinical studies on asthmatic horses, may not be attributed to the modification of the adaptive response.